(untitled) (Medicine Today, 2023)
Introduction with aim and objectives: Cerebrovascular diseases have recently emerged as a major health problem affecting the elderly population. The spectrum includes some of the most common and devastating disorders like ischemic stroke, hemorrhagic stroke and anomalies in vascular system. Microalbuminuria is an early finding in urine in the patients of diabetes and hypertension and it is associated with macrovascular complications like cerebrovascular accident and myocardial infarction. The aim of this study was to find out the pattern and frequency of microalbunuria with different types of stroke. Materials and Methods: Fifty cases of stroke Patients admitted in CMCH medicine and neurology department from 1 January 2019 to 31 June 2019 were analyzed and urine for microalbumin was done. Univariate statistical analyses were performed to see the outcome in relation with blood volume by SPSS-19. Results: Regarding analysis of gender distribution of 50 study patients, 27(60%) were found male and 23(40%) were found female. Male to female ratio was 1:0.4. Among the 50 patients, different types of occupation were found. House wife was common occupation. Among the total patients, most of them were from lower middle class 24(61.4%). Others were from low 16(32.0%) and upper middle class 10(5.75%) group. Most of the patients were from rural residence 41(80%). In our study, 13(71.42%) patients had hypertension. Diabetes mellitus was found among 13(8.57%). Different examination findings were analyzed where mean GCS of ischaemic stroke was 14.5 and mean GCS of hemorrhagic stroke was 10.6, 12 patients had abnormal fundoscopic findings. Regarding analysis of serum LDL and serum Creatinine, mean LDL level was 123.95 and mean serum Creatinine level was 1.19. After analysis, mean of urine for Microalbumin of 30 Ischaemic stroke patients was 71.96mg/L and mean of urine for Microalbumin of 20 Hemorrhagic stroke patients was 80.70mg/L. Conclusions: We found high frequency of microalbuminuria in patients with stroke Therefore; microalbuminuria could be is a useful modifiable factor, in addition to conventional risk factors, in identifying those at increased risk of stroke. Medicine Today 2023 Vol.35(1): 63-66